A systematic compilation of endemic flora in Nigeria for conservation management - T.I. Borokini (Journal of Threatened Taxa, 2014)
Endemic species with limited geographical ranges are more susceptible to extinction than widely ranging species, and effective conservation management of endemic species requires detailed knowledge of their status and distribution.  This study was conducted to assemble a comprehensive list of flora endemic to Nigeria. While earlier reports listed as many as 205 endemic plant species, only 91 species belonging to 44 families were found in this study, with Rubiaceae accounting for the highest number of species.  The list contains 23 trees, 26 herbs, 22 shrubs, 14 epiphytic orchids and bryophytes, three vines and three ferns.  The Oban Division of the Cross River National Park houses 41 endemic plants, while other notable locations for endemic flora include Eket, Naraguta, Degema, Idanre hills, Ukpon River Forest Reserve, Calabar and Anara Forest Reserve.  Only 15 of the endemic plants are listed in the IUCN Red List of Threatened Species version 2013.2, ranging from Vulnerable to Critically Endangered.